The Politics of Protestant Churches and the Party-State in China: God Above Party? - Vala, Carsten T. (Routledge Research on the Politics and Sociology of China, 2017)
From domination to negotiation from 1949 to today: declining state capacity, rising Protestant numbers -- The role of official associations: projecting a façade of domination in the public transcript -- Resisting the official agenda, sharing grassroots values: the spread of Protestant groups -- Cultivating social capital as a resource for Protestant resistance -- Enlarging the bounds of the public transcript: founding large, public urban churches -- Repression of an urban church Shanghai's Wanbang Church -- Challenging the bounds of the public transcript -- Beijing Shouwang Church.